Antecedents and consequences of liking in retail service relationships in China and Greece. Issue 3 (June 2017) - Abosag, Ibrahim; Baker, Thomas L.; Hall, Kristina Lindsey; Voulgari, Aliki-Dimitra; Zheng, Xiaoyuan
Highlights: This study is the first to examine the concept of liking in the financial retail service relationships cross-culturally. This study developed new scale on measuring liking within the financial retail services that can be used for cross-cultural studies. This study developed and tested the conceptual model of the antecedents and consequences of liking in the financial retail service relationships within China and Greece. The findings show great deal of similarities between the Chinese and Greek samples with minor but important differences. Abstract: The marketing literature has provided a limited examination of the concept of liking, and even this has mainly occurred within business-to-business or advertising contexts. In this paper, the authors propose a model of the intervening role of liking in the customer-service provider relationship in two countries, China and Greece. The antecedents of liking include three key service constructs, namely customer education, customer participation, and service quality. The outputs of liking are proposed to be affective trust and affective commitment, which in turn influence (behavioral) loyalty. The research model is tested using samples from China (N = 277) and from Greece (N = 306). The model is largely supported in both samples. Therefore, the authors suggest that liking in financial services has an important role in the customer-service provider relationship. Implications for international businesses are discussed.